PENGEMBANGAN DATABASE DI ERA DIGITAL - Royhan Zaki Ramadhana; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Competition between businesses in this digital era is getting tighter and tougher. Business people must be able to utilize information technology to increase productivity and produce superior products. More than that, business people must also be able to utilize this technology to build business intelligence to increase their competitiveness. The data overflow phenomenon that occurs in this digital era must be able to be transformed into knowledge that is useful for technological progress. Therefore, business people must be able to apply big data technology to be able to manage data in large amounts, variety and very quickly. One of the big data technology ecosystems that plays an important role in data management is NoSQL databases. NoSQL databases are divided into four categories. Two of the most popular are document-oriented NoSQL databases and column-oriented NoSQL databases. So that big data technology can process internal data, it is necessary to have a good database transformation method to migrate data from RDBMS to NoSQL database. Several studies have been carried out on this matter.